Can sport clubs be represented? Pre-packed policy advocacy and the trade-offs for democratic responsiveness. Issue 4 (1st October 2020) - Stenling, Cecilia; Sam, Mike
ABSTRACT: Federative sport organisations are increasingly conducting advocacy vis-à-vis public authorities on behalf of their membership, but the meaning and implications of such interest representation are unclear. The purpose of this paper is therefore to explore how representatives of sport federations understand interests in the context of sport advocacy, and the transformative effects on future representational and wider democratic practices that may follow from such conceptualisations. Drawing theoretically on a distinction between attached and objective interests, and empirically on interviews with 46 Swedish Regional Sport Federation representatives, we show that interests are understood as best derived from central policy documents and edicts rather than clubs' immediate wishes. This centralised sourcing of advocacy issues may be explained with reference to the legitimacy representatives believe that the internal democratic system bestows on processes of issue prioritisation. In the absence of bottom-up practices outside of general assemblies to channel federated clubs' interests, this issue prioritisation strategy involves a shift from accommodating interests attached to clubs to promoting understandings of sport's collective and 'objective' interest. The significance of this shift is twofold. First, it enables the justification of a professionalised, bureaucratic and centralised advocacy dedicated to increasing advocacy impact rather than 'downward' representational authorisation and accountability . Second, it may shape what is perceived as legitimate subsequent representation, including the appropriate participatory practices associated with advocacy. More generally, if clubs and their members come to understand their interests as objective, their capacity and will to formulate their interests as attached may be further weakened.